2019
DOI: 10.1073/pnas.1815423116
|View full text |Cite|
|
Sign up to set email alerts
|

Primitive Old World monkey from the earliest Miocene of Kenya and the evolution of cercopithecoid bilophodonty

Abstract: Old World monkeys (Cercopithecoidea) are a highly successful primate radiation, with more than 130 living species and the broadest geographic range of any extant group except humans. Although cercopithecoids are highly variable in habitat use, social behavior, and diet, a signature dental feature unites all of its extant members: bilophodonty (bi: two, loph: crest, dont: tooth), or the presence of two cross-lophs on the molars. This feature offers an adaptable Bauplan that, with small changes to its individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Phylogenetics. The composite near-comprehensive tree of Afro-Arabian primates, anomaluroid rodents, and hystricognathous rodents combines information from multiple BTD analyses of character matrices published by Gunnell et al 22 , Rasmussen et al 60 , Dembo et al 61 , DeSilva et al 62 , Sallam and Seiffert 25 , and Marivaux et al 16 . The tree is supplemented by molecular phylogenies of extant taxa 59,63 , and grafting of several extinct taxa that were not included in any of the aforementioned phylogenetic character matrices.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetics. The composite near-comprehensive tree of Afro-Arabian primates, anomaluroid rodents, and hystricognathous rodents combines information from multiple BTD analyses of character matrices published by Gunnell et al 22 , Rasmussen et al 60 , Dembo et al 61 , DeSilva et al 62 , Sallam and Seiffert 25 , and Marivaux et al 16 . The tree is supplemented by molecular phylogenies of extant taxa 59,63 , and grafting of several extinct taxa that were not included in any of the aforementioned phylogenetic character matrices.…”
Section: Methodsmentioning
confidence: 99%
“…Additional CladeAge calibration Another fossil species from Nsungwe 2B is Nsungwepithecus gunnelli, currently known from a single specimen (RRBP 11178), a left partial mandible with a lower m3 (Stevens et al, 2013). Nsungwepithecus was not included in the phylogenetic analyses by Stevens et al (2013), but they report the presence of numerous lower molar synapomorphies that are shared with "victoriapithecid" cercopithecoids ("Victoriapithecidae" is a paraphyletic assemblage of stem cercopithecoids in the phylogenetic analyses of Stevens et al (2013) and Rasmussen et al (2019)), such as deeply incised buccal clefts, a high degree of buccal flare, and the lack of a buccal cingulid. Rasmussen et al (2019) confirmed the stem cercopithecoid position of Nsungwepithecus in their phylogenetic analysis, but they argued that the phylogenetic position of Nsungwepithecus should be regarded as tentative until more material is available.…”
Section: Calibrating Taxon Rukwapithecus Fleagleimentioning
confidence: 99%
“…By contrast, even in the most recent morphological datasets for primate phylogenetics (at least, those focused on higher level relationships, e.g., between families), extant taxa are typically scored at the genus level, or only a single species-level representative of each genus is included (e.g. Rasmussen et al, 2019;Gilbert et al, 2020;Seiffert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cercopithecid primates evolved in Africa approximately 23 million years ago (MA; Figure 1; Frost, 2017). Although the earliest cercopithecid fossil remains are all isolated teeth dated to ~20 MA (Rasmussen et al, 2019), molecular evidence dates the divergence of Cercopithecinae and Colobinae to approximately 18 MA, after which both clades quickly diversified and expanded out of Africa and across Europe and Asia (Frost, 2017). In addition to being the most speciose primate family, and sister taxon to apes (Hominoidea), the genetics and developmental biology of cercopithecids have been well-studied in biomedical literature (VandeBerg, Williams-Blangero, & Tardif, 2009).…”
mentioning
confidence: 99%